Communications - Shenson, Howard L.; Cook, Doris M.; Hunt, J. G.; Blanchard, Kenneth H. (Academy of Management Journal, 1969)
This article comments on the paper ?The Impact on Managers of Frequency of Feedback,? by Doris M. Cook. The article is believed to be an example of over reliance on the obvious and a failure to control or test for relevant variables. For a long time, management theorists have argued that frequent feedback has a positive impact on the communication process and the effectiveness of an organization. Cook's findings may be significant because they correlate with several external variable. However, correlation only implies a relationship and not causality.